Tolerance of Chemoorganotrophic Bioleaching Microorganisms to Heavy Metal and Alkaline Stresses - Annick Monballiu; Nele Cardon; Minh Tri Nguyen; Christel Cornelly; Boudewijn Meesschaert; Yi Wai Chiang (Bioinorganic Chemistry and Applications)
The bioleaching potential of the bacterium Bacillus mucilaginosus and the fungus Aspergillus niger towards industrial residues was investigated by assessing their response towards various heavy metals (including arsenic, cadmium, cobalt, chromium, nickel, lead, and zinc) and elevated pH. The plate diffusion method was performed for each metal to determine the toxicity effect. Liquid batch cultures were set up for more quantitative evaluation as well as for studying the influence of basicity. Growth curves were prepared using bacterial/fungal growth counting techniques such as plate counting, optical density measurement, and dry biomass determination. Cadmium, nickel, and arsenite had a negative influence on the growth of B. mucilaginosus, whereas A. niger was sensitive to cadmium and arsenate. However, it was shown that growth recovered when microorganisms cultured in the presence of these metals were inoculated onto metal-free medium. Based on the findings of the bacteriostatic/fungistatic effect of the metals and the adaptability of the microorganisms to fairly elevated pH values, it is concluded that both strains have potential applicability for further research concerning bioleaching of alkaline waste materials.